(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract 2 Breastfeeding problems that can arise during the postpartum period are breast engorgement pain. The pain in the breast can make the mother and baby feel uncomfortable. Non-pharmacological methods that can be used to reduce the pain of swelling of the breast are cabbage compresses and warm compresses. The purpose of this study is to determine The effect of cabbage compresses and warm compresses to reduce pain intensity in breast engorgement. The study was conducted in March 2019 - June 2019 in the Teratai Room of Arifin Achmad Hospital, Riau Province. This type of research is quasi-experimental with a pretest-posttest two group design. post partum which was treated in the Teratai Room of the Arifin Achmad Hospital, Riaud Province with a sample of 10 respondents in the cabbage compress group and 10 respondents in the warm compress group who were taken by purposive sampling technique. Collecting data using an observation sheet containing a pain scale Numeric Rating Scale (NRS). The results showed that the average pain intensity before the cabbage compress and before the warm compress was 5.7 (SD 1.34) and after being given treatment the results were obtained on the cabbage compress 2. , 9 (SD 1.10) and warm compresses 4.1 (SD 1.28). The results of statistical tests showed that there was a difference in the pain intensity of breast swelling after being treated between hot compresses and warm compresses in the Teratai room of Arifin Achmad Hospital, Riau Province (p = 0.042), cabbage compresses were more effective in reducing pain than warm compresses. It is suggested to the management of Arifin Achmad Hospital to consider giving cabbage compresses as an effective and economical non-pharmacological method in reducing the pain of breast swelling in post partum mothers.